2014
DOI: 10.1186/s40405-014-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

Senior gambling in Hong Kong: through the lenses of Chinese senior gamblers – an exploratory study

Abstract: The meanings of gambling among senior gamblers in Hong Kong were investigated using semi-structured interviews based on an ethnographic approach. 18 senior gamblers (10 men; 8 women) over the age of 55 years were asked to describe their childhood, adolescent and early adult experience and developmental history of gambling and gambling trajectories. They also completed the Problem Gambling Severity Index (PGSI) of the Canadian Problem Gambling Index. Most senior gamblers (n = 15) were non-problem gamblers, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
3
13
0
1
Order By: Relevance
“…The role of family has also been identified in a qualitative study on Australian gamblers who reported that gambling was a frequent activity in their family, and that it was regarded as a pastime that helped family bonding ( Victorian Responsible Gambling Foundation, 2012 ). In their study on older adult gamblers in Hong Kong, Ohtsuka and Chan ( 2014 ) similarly found that many of the older adults started gambling when they were young and that gambling was considered a part of family activities. There was no stigma associated with gambling; in fact, it was associated with positive memories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of family has also been identified in a qualitative study on Australian gamblers who reported that gambling was a frequent activity in their family, and that it was regarded as a pastime that helped family bonding ( Victorian Responsible Gambling Foundation, 2012 ). In their study on older adult gamblers in Hong Kong, Ohtsuka and Chan ( 2014 ) similarly found that many of the older adults started gambling when they were young and that gambling was considered a part of family activities. There was no stigma associated with gambling; in fact, it was associated with positive memories.…”
Section: Discussionmentioning
confidence: 99%
“…Magoon and Ingersoll ( 2006 ) found that parental gambling was related to levels of past year gambling as well as an increased likelihood of being classified as a problem gambler among adolescent gamblers. Ohtsuka and Chan ( 2014 ) in their study on older adult gamblers in Hong Kong found that older adults had often been introduced at a young age to gambling by extended family members. Gambling was an accepted behavior in their families and was not stigmatized; furthermore, development of gambling skills was even encouraged at a young age.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly they opined that cultures that have negative attitudes towards getting professional help are less likely to try and get help when they initially begin experiencing problems with their gambling and, thus are more likely to continue gambling and subsequently develop problem gambling. A recent study of gambling among older adults in Hong Kong concluded that the elderly gamblers in Hong Kong ‘share the social space created through gambling with fellow senior gamblers, which seems to provide social interactions in the form in which they are comfortable to participate and that gambling may provide an existential meaning to their lives in the hectic city life of Hong Kong’ ( Ohtsuka and Chan, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gambling is defined as "risking something of value on the unknown outcome of some future event…, the ultimate hope of gambling is to realize a value greater than that risked" (Aasved 2003, p. 3 (Ohtsuka and Chan 2014). The benefits include a channel for social interaction and meaningful relationships.…”
Section: The State Of Gambling In Hong Kong and Macaomentioning
confidence: 99%
“…Ohtsuka and Chan (2014) investigated the significance of gambling among senior gamblers in Hong Kong. Ohtsuka and Chan (2014) investigated the significance of gambling among senior gamblers in Hong Kong.…”
Section: Elderlymentioning
confidence: 99%